2020
DOI: 10.1021/acs.jpclett.0c02779
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Voltammetry of Bulk CO Electrooxidation in Neutral Media through Combined SECM Measurements

Abstract: Recently, the bulk electrooxidation of CO on gold or platinum has been used to detect CO produced during CO 2 reduction in neutral media. The CO bulk oxidation voltammetry may show two distinct peaks depending on the reaction conditions, which up to now have not been understood. We have used scanning electrochemical microscopy (SECM) to probe CO oxidation and pH in the diffusion layer during CO 2 reduction. Our results show that the two different peaks are due to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 26 publications
(67 reference statements)
2
41
0
Order By: Relevance
“…However, in our case, at low current densities, and low pH, due to the lower mass transport limitation in the GDE configuration, the activity for CO (and corresponding production of OH − ) is not high enough to neutralize the protons diffusing towards the catalyst surface, favouring hydrogen production. On the other hand, at current densities above 50 mA cm −2 , especially for bulk pH 3 or 4, the local acidic environment can be rapidly neutralized 23 , 24 , enabling FEs for CO above 80%. We see that when starting from bulk pH 2, higher current densities are required to achieve this suppression of proton reduction.…”
Section: Resultsmentioning
confidence: 99%
“…However, in our case, at low current densities, and low pH, due to the lower mass transport limitation in the GDE configuration, the activity for CO (and corresponding production of OH − ) is not high enough to neutralize the protons diffusing towards the catalyst surface, favouring hydrogen production. On the other hand, at current densities above 50 mA cm −2 , especially for bulk pH 3 or 4, the local acidic environment can be rapidly neutralized 23 , 24 , enabling FEs for CO above 80%. We see that when starting from bulk pH 2, higher current densities are required to achieve this suppression of proton reduction.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, in our recent studies, we have used a Pt-UME in the surface-generation tip-collection (SG-TC) mode to detect CO produced during CO 2 RR on Au, Cu and Ag electrodes. 25,26 Although these previous measurements were performed on non-permeable substrates, we could also demonstrate that probing the local hydroxide and water activities during the oxygen reduction reaction (ORR) and CO 2 RR on GDEs can be achieved with SECM by shear-force positioning of Pt nanoelectrodes at ~100 nm above the GDE surface. [23,24] This experimental approach allows for simultaneously deriving modulations of the local pH value in correlation with the current density, and the topography in situ and with high resolution.…”
Section: Introductionmentioning
confidence: 90%
“…In contrast, scanning probe techniques are powerful tools for investigating activity locally with high resolution. [19][20][21][22][23][24][25][26] Mayer et al 22 used a Pt ultramicroelectrode (Pt-UME) to detect formate, CO and H 2 during CO 2 RR on Sn/SnO x arrays. However, the tip-to-surface distance was determined using O 2 reduction diffusion limitation, which is only practical for probing flat electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the local ion activity changes, one also needs to consider that the predominant product of the CO 2 RR at a Ag‐GDE is CO, which may poison the Pt tip surface. However, by sweeping the potential anodically, adsorbed CO is removed, which re‐establishes a clean Pt tip in each potentiodynamic cycle [29] . We found that ultraclean Pt tips are necessary for the anticipated measurements above CO 2 ‐converting electrodes, since otherwise often ambiguous Pt voltammograms are observed (Figure S3).…”
Section: Figurementioning
confidence: 97%
“…However, by sweeping the potential anodically,a dsorbed CO is removed, which re-establishes ac lean Pt tip in each potentiodynamic cycle. [29] We found that ultraclean Pt tips are necessary for the anticipated measurements above CO 2 -convertinge lectrodes, since otherwise often ambiguous Pt voltammograms are observed (Figure S3). The cathodic shift of the PtO red.…”
mentioning
confidence: 95%